Current transcatheter devices to treat functional tricuspid regurgitation with discussion of issues relevant to clinical trial design - Hahn, Rebecca T. (Annals of Cardiothoracic Surgery, 2017)
Functional or secondary tricuspid regurgitation (TR) has seen increased attention in recent times as relationships with clinically-relevant outcomes have come to light. Despite the association of increased mortality with significant TR, the disease remains under-recognized and thus relatively untreated. In addition, the disease itself has not been extensively studied and the interactions between annular dilatation, right heart disease and pulmonary hypertension are poorly understood. However, the high mortality and recurrence rate with current surgical replacement or repair techniques is well recognised, opening the door to transcatheter therapies for functional TR. The current perspective reviews the rationale for transcatheter solutions, describes some of the current approaches and discusses the ongoing questions of a poorly-studied condition which may limit the design of clinical trials for this disease.